Scanning Electrochemical Microscopy Meets Optical Microscopy: Probing the Local Paths of Charge Transfer Operando in Booster-Microparticles for Flow Batteries - Moghaddam, Mahdi (Wiley-VCH, 2025)
Understanding the oxidation/reduction dynamics of secondary microparticles formed from agglomerated nanoscale primary particles is crucial for advancing electrochemical energy storage technologies. In this study, the behavior of individual copper hexacyanoferrate (CuHCF) microparticles is explored at both global and local scales combining scanning electrochemical microscopy (SECM), for electrochemical interrogation of a single, but global-scale microparticle, and optical microscopy monitoring to obtain a higher resolution dynamic image of the local electrochemistry within the same particle. Chronoamperometric experiments unveil a multistep oxidation/reduction process with varying dynamics. On the one hand, the global SECM analysis enables quantifying the charge transfer as well as its dynamics at the single microparticle level during the oxidation/reduction cycles by a redox mediator in solution. These conditions allow mimicking the charge storage processes in these particles when they are used as solid boosters in redox flow batteries. On the other hand, optical imaging with sub-particle resolution allows the mapping of local conversion rates and state-of-charge within individual CuHCF particles. These maps reveal that regions of different material loadings exhibit varying charge storage capacities and conversion rates. The findings highlight the significance of porous nanostructures and provide valuable insights for designing more efficient energy storage materials.